New Pd(ii)-pincer type complexes as potential antitumor drugs: synthesis, nucleophilic substitution reactions, DNA/HSA interaction, molecular docking study and cytotoxic activity - Pavlović, Sladjana; Petrović, Biljana; Ćoćić, Dušan; Scheurer, Andreas; Sretenović, Snežana; Nešić, Maja D.; Nišavić, Marija; Maric, Zorana; Stanisavljević, Isidora; Ćorović, Irfan; Simović Marković, Bojana; Maric, Veljko; et al. (Dalton Transactions, 2024)
Two new complexes of Pd(ii), [Pd(L1)Cl]Cl (Pd1) and [Pd(L2)Cl]Cl (Pd2), (where L1 = N2,N6-bis(5-methylthiazol-2-yl)pyridine-2,6-dicarboxamide and L2 = N2,N6-di(benzo[d]thiazol-2-yl)pyridine-2.6-dicarboxamide) were synthesized. Characterization of the complexes was performed using elemental analysis, IR, 1H NMR spectroscopy and MALDI-TOF mass spectrometry. The nucleophilic substitution reactions of complexes with l-Methionine (l-Met), l-Cysteine (l-Cys) and guanosine-5′-monophosphate (5′-GMP) were studied by stopped-flow method at physiological conditions (pH = 7.2 and 37 °C). Complex Pd1 was more reactive than Pd2 in all studied reactions, while the order of reactivity of the selected ligands was: l-Met > l-Cys > 5′-GMP. The interaction of complexes with calf thymus-DNA (CT-DNA) was studied by Uv-Vis absorption and fluorescence emission spectroscopy. Competitive binding studies with intercalative agent ethidium bromide (EB) and minor groove binder Hoechst 33258 were performed as well. Both complexes interacted with DNA through intercalation and minor groove binding, where the latter was preferred. Additionally, the interaction of Pd1 and Pd2 complexes with human serum albumin (HSA) was studied employing fluorescence quenching spectroscopy. The results indicate a moderate binding affinity of complexes, with slightly stronger binding of the Pd1. Fluorescence competition experiments with site-markers (eosin Y and ibuprofen) for HSA were used to locate the binding site of Pd1 to the HSA. Additionally, the interaction with DNA and HSA was studied by molecular docking and the revealed results were in good agreement with the experimentally obtained ones. Pd1 complex exhibited cytotoxicity toward human (HCT116) and mouse cell lines (CT26) of colorectal cancer, mouse (4T1) and human (MDA-MB468) breast cancer lines and non-cancerous mouse mesenchymal stem cells (mMSC). In addition, Pd1 complex demonstrated significant selectivity towards cancer cells over non-cancerous mMSC, indicating a high potential to eliminate malignant cells without affecting normal cells. It induced apoptosis in CT26 cells, effectively arrested the cell cycle in the S phase, and selectively down-regulated cyclin D and cyclin E. Moreover, it can alter the expression of cell cycle regulators by increasing p21 and decreasing p-AKT. These findings confirm its ability to disrupt key tumor cell survival signals and suggest that the Pd1 complex is a potent candidate for effective cancer treatment.
CRIS-Team Scopus Importer:2025-02-04